A fluorescent and colorimetric dual-recognition probe based on copper(ii)-decorated carbon dots for detection of phosphate. Issue 42 (12th October 2021) - Gao, Xue; Sun, Minjun; Liu, Xiuying; Zhong, Keli; Tang, Lijun; Li, Jianrong
Abstract : In the present article, we report a novel fluorescent and colorimetric dual-signal sensing probe based on a CD–Cu 2+ complex for the detection of the phosphate ion (Pi). Abstract : In the present article, we report a novel fluorescent and colorimetric dual-signal sensing probe based on a CD–Cu 2+ complex for the detection of the phosphate ion (Pi). The yellow fluorescent carbon quantum dots (CDs) were simply synthesized via one-step hydrothermal treatment of o -phenylenediamine (OPD) and 4-aminobutyric acid (GABA). The method was based on the combination of the CDs and Cu 2+ to form a coordination complex. Pi can capture Cu 2+ on the surface of CDs, which brings about two kinds of signal change through competitive complexation, including fluorescence and UV-vis absorption. The probe could detect the Pi with a linear range of 0.01–1 mM with a detection limit of 3.75 μM for the fluorescence signal and a linear range of 0.01–1 mM with a detection limit of 4.38 μM for the colorimetric signal. And the change in absorption signal can be used to visually detect Pi. Furthermore, the proposed sensing system was successfully applied to determine Pi in practical water samples.